The nuclear option ; I wanna be in America ; The making of an image [videorecording] - Lazaro, Cheche (The Probe Team, 1993)
The Philippines suffered a setback in its fight against Westinghouse when it lost the bribery suit it field against the Marcoses. A Filipino-American immigration expert and the U.S. Consul-General warns the illegal activities of Filipinos going abroad. A look at the works of Filipino fashion photographers.